Faith beyond reason - Evans, C. Stephen (Edinburgh : Edinburgh University Press, 1998)
Can a 'leap' of faith be justified? Ought we not to reject anything for which there is no evidence? C. Stephen Evans distinguishes between a faith which rejects all reason and a faith requiring that reason is self-critical. In this accessible book he addresses this central debate in the philosophy of religion in the light of the key arguments from Kierkegaard, Aquinas and Kant. The text leads the student gently through the traditional topics, such as knowledge of God's existence, the problem of evil, and how someone could know that his or her religion had been based on revelation from God.
Frontmatter -- Contents -- Preface -- 1 Introduction: The Problem of Faith and Reason -- 2 Fideism as Irrationalism -- 3 Faith Without Reasons: Is Faith Based on Evidence? -- 4 Faith Above Reason: Aquinas -- 4 Faith Above Reason: Aquinas -- 6 Faith Above Reason: Kierkegaard -- 7 Faith Against Reason: Kierkegaard -- 8 A Fideistic Account of Knowing God -- 9 Faith and the Problem of Evil -- 10 Faith and Doctrines Known by Revelation -- Bibliography -- Index
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Kierkegaard, Søren, -- 1813-1855 -- Religion; Kierkegaard, Søren, -- 1813-1855; Faith and reason -- Christianity; RELIGION -- Faith; Faith and reason -- Christianity; Religion; Godsdienst; Rationaliteit; Fideïsme.